Chaperonin GroEL/GroES Over-Expression Promotes Aminoglycoside Resistance and Reduces Drug Susceptibilities in Escherichia coli Following Exposure to Sublethal Aminoglycoside Doses - Goltermann, Lise; Sarusie, Menachem V.; Bentin, Thomas (Frontiers in Microbiology, 2016)
Antibiotic resistance is an increasing challenge to modern healthcare. Aminoglycoside antiobiotics cause translation corruption and protein misfolding and aggregation in Escherichia coli. We previously showed that chaperonin GroEL/GroES depletion and overexpression sensitize and promote short-term tolerance, respectively, to this drug class. Here we show that chaperonin GroEL/GroES over-expression accelerates acquisition of aminoglycoside resistance and multi-drug resistance following sub-lethal aminoglycoside antibiotic exposure. Chaperonin buffering could provide a novel mechanism for antibiotic resistance and multi-drug resistance development.